2012
DOI: 10.1111/j.1755-3768.2012.02536.x
|View full text |Cite
|
Sign up to set email alerts
|

Two-year follow-up of a randomized trial of spectacles plus alternate-day patching to treat strabismic amblyopia

Abstract: ABSTRACT.Purpose: To compare spectacles plus alternate-day patching for 8 hr or more with spectacles plus patching for 8 hr or more 6 days weekly to treat strabismic amblyopia 1 year after a 1-year randomized trial. Methods: Forty children (mean age, 4.3 years) participated. Refractive correction was provided. The children were assigned to alternate-day patching for 8 hr or more or patching for 8 hr or more daily 6 days weekly. VA, binocular function, and refractive errors were measured after 2 years. The main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…It typically affects 3% of the population, depending on the definition (Attebo et al 1998;Wang et al 2000). Early detection of amblyopia along with improvement in treatment and compliance (Agervi et al 2010(Agervi et al , 2013 has been found to be associated with a decreased prevalence of amblyopia (Kvarnstr€ om et al 1998;Eibschitz-Tsimhoni et al 2000;Williams et al 2002;Carlton et al 2008;Beauchamp et al 2010;de Koning et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It typically affects 3% of the population, depending on the definition (Attebo et al 1998;Wang et al 2000). Early detection of amblyopia along with improvement in treatment and compliance (Agervi et al 2010(Agervi et al , 2013 has been found to be associated with a decreased prevalence of amblyopia (Kvarnstr€ om et al 1998;Eibschitz-Tsimhoni et al 2000;Williams et al 2002;Carlton et al 2008;Beauchamp et al 2010;de Koning et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The types of amblyopia targeted in included studies ranged from childhood amblyopia [1, 11–42] to residual amblyopia in older children [43, 44], adolescents or adults [40, 41, 45, 46], unilateral [3, 12] and bilateral [3], refractive [3], anisometropic [19, 23], strabismic [24, 47], and stimulus deprivation amblyopia [48].…”
Section: Resultsmentioning
confidence: 99%
“…Interventions varied from the “gold standard” refractive correction and occlusion or atropine penalization [24, 27, 30, 31] to the more modern controversial treatments such as low-level laser [46], photic stimulation [43], and medical and behavioural treatment [45] which were more likely to be used beyond the visual maturation age when conventional treatments often fail.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations